Pola Penggunaan Insulin Pada Pasien Diabetes Melitus Tipe 2 Rawat Inap Di Rumah Sakit X Pekanbaru Tahun 2014 - Inayah Inayah; M. Yulis Hamidy; Roza Putri Rachma Yuki (Jurnal Ilmu Kedokteran, 2016)
Insulin is one of pharmacological treatment of type 2 diabetes mellitus (DM). The aim of this study was to know thepattern of insulin use in hospitalized patients with type 2 diabetes Hospital X Pekanbaru. The type of research wasdescriptive. Data retrieved from 63 the medical records of patients with type 2 diabetes at Hospital X Pekanbaruperiod January - December 2014. The most characteristics of subject was average of age 55.40 (± 10.91) years, theaverage of RBG level 313.37 (± 135.81) mg / dL, female (55.6%), financing with BPJS (49.2%), housewives (49.2%),the diagnosis of type 2 diabetes with complications (38.1 %). The most insulin usage according to duration of actionwas short-acting insulin (46.4%), the number of daily doses was <20 IU from all type of insulin. The most combinationof different insulin types (7.9%) was long-acting insulin with rapid-acting insulin and the most combination of insulinand OHD (6.3%) was a short-acting insulin with gluconeogenesis inhibitor and premixed insulin with gluconeogenesisinhibitor.